One dimensional heat transfer through rectangular fin using finite element method (FEM) - Maryam 'Azyyati Ab Aziz (Institute of Engineering Mathematics, 2016)
The objectives of this study are to develop FEM algorithm using MATLAB for 1-D heat transfer problem; to apply this algorithm to solve 1-D heat transfer problem; to find the numerical and exact result and compare the result; to find the difference the effect of having different number of nodes and different fin length; to apply the algorithm for the same problem using two different material properties.